Pediatric nursing and the family approach: subsidies for undergraduate teaching (Revista Latino-Americana de Enfermagem, 2002)
This work aims at presenting the instruments used in the family nursing approach as depicted in the international literature as well as at providing subsidies for their utilization by Brazilian nursing professionals in family health approaches to child care. The authors present the experience of introducing a methodology for systematized care in Pediatric Nursing programs using instruments for data collection such as the family APGAR, Genogram and Ecomap. They argue that these instruments do not replace the theoretical basis of care or the reason and discernment in order to provide data with meaning and find better solutions to care for children and their family.